Cross section and resonance effects in photoemission from Sn-doped In2O3(111) - Zhang, K; Payne, D; Egdell, R (2012)
Photoemission spectra of Sn-doped In 2O 3(111) have been measured using a range of photon energies between 40 and 1300 eV. The intensity of structure at the bottom of the valence band associated with states of mixed Sn 5s/O 2p character increases with increasing photon energy relative to that of states of more dominantly O 2p character at the top of the valence band, as expected from one electron ionisation cross sections. In addition a pronounced resonance in the intensity of a weak conduction band feature is observed around the In 4p core threshold. © 2011 Elsevier Ltd. All rights reserved.